A new Batillipes (Tardigrada, Heterotardigrada, Batillipedidae) from North Portugal (Atlantic Ocean) - Rubal M. (2017)
The knowledge of marine tardigrades in the Iberian Peninsula is very scarce in comparison with those from limno-terrestrial environments. As part of an effort to improve the knowledge of marine tardigrades in the Iberian Peninsula, a new species of marine tardigrade, Batillipes minius sp. nov., is described from shallow subtidal coarse sand collected at Moledo, Northern Portugal, close to the mouth of the Minho river. The new species differs from all other Batillipes species by its combination of toe pattern, dorsal and ventral lateral projections, caudal apparatus, cuticle segmentation and the presence of a dorsal indentation in its head. This new species was found in well-oxygenated, shallow subtidal, medium-coarse sand with low organic matter content. © 2016, Senckenberg Gesellschaft für Naturforschung and Springer-Verlag Berlin Heidelberg.